David Pareus irénikus hatása a magyar protestáns egyházakra - Olga LUKÁCS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Irenic Influence of David Pareus over the Hungarian Protestant Churches.